A Thermostable, Modified Cathelicidin-Derived Peptide With Enhanced Membrane-Active Activity Against Salmonella enterica serovar Typhimurium - Klubthawee, Natthaporn; Aunpad, Ratchaneewan (Frontiers in Microbiology, 2021)
Foodborne illness caused by consumption of food contaminated with Salmonella is one of the most common causes of diarrheal disease and affects millions of people worldwide. The rising emergence and spread of antimicrobial resistance, especially in some serotypes of Salmonella, has raised a great awareness of public health issues worldwide. To ensure safety of the food processing chain, the development of new food preservatives must be expedited. Recently, thermal- and pH-stable antimicrobial peptides have received much attention for use in food production, and represent safe alternatives to chemical preservatives. A 12-mer cathelicidin-derived, α-helical cationic peptide, P7, displayed rapid killing activity, against strains of drug-resistant foodborne Salmonella enterica serovar Typhimurium and its monophasic variant (S. enterica serovar 4,5,12:i:-) and had minimal toxicity against mouse fibroblast cells. P7 tended to form helical structure in the membrane-mimic environments as evaluated by Circular dichroism (CD) spectroscopy. The action mode of P7 at the membrane-level was affirmed by the results of flow cytometry, and confocal, scanning and transmission electron microscopy. P7 killed bacteria through binding to bacterial membranes, penetration and the subsequent accumulation in S. enterica serovar Typhimurium cytoplasm. This induced membrane depolarization, permeabilization, and sequential leakage of intracellular substances and cell death. Except for sensitivity to proteolytic digestive enzymes, P7 maintained its inhibitory activity against S. enterica serovar Typhimurium in the presence of different conditions [various salts, extreme pHs and heat (even at 100°C)]. Moreover, the peptide is unlikely to induce bacterial resistance in vitro. Taken together, this study demonstrated that the membrane-permeabilizing P7 peptide has much potential as a new antimicrobial agent for use in food processing and preservation.